![\qquad\qquad\huge\underline{{\sf Answer}}♨](https://tex.z-dn.net/?f=%5Cqquad%5Cqquad%5Chuge%5Cunderline%7B%7B%5Csf%20Answer%7D%7D%E2%99%A8)
Let's simplify ~
![\qquad \sf \dashrightarrow \:( - 2 - 5i) - ( - 4 + 6i)](https://tex.z-dn.net/?f=%5Cqquad%20%5Csf%20%20%5Cdashrightarrow%20%5C%3A%28%20-%202%20-%205i%29%20-%20%28%20-%204%20%2B%206i%29)
![\qquad \sf \dashrightarrow \: - 2 - 5i + 4 - 6i)](https://tex.z-dn.net/?f=%5Cqquad%20%5Csf%20%20%5Cdashrightarrow%20%5C%3A%20-%202%20-%205i%20%2B%20%204%20%20-%20%206i%29)
![\qquad \sf \dashrightarrow \: - 2 + 4 - 5i- 6i)](https://tex.z-dn.net/?f=%5Cqquad%20%5Csf%20%20%5Cdashrightarrow%20%5C%3A%20-%202%20%2B%20%204%20%20%20-%205i-%20%206i%29)
![\qquad \sf \dashrightarrow \:2 - 11i](https://tex.z-dn.net/?f=%5Cqquad%20%5Csf%20%20%5Cdashrightarrow%20%5C%3A2%20-%2011i)
Therefore, A is the Correct choice !
Answer:
vvvvvvvvvvvvvvvvvvvvvvvvvvvvvvvvvvvvvvvvvvvvvvvvvvvvvvvvvvvvvvvvvv=kkkkk
Step-by-step explanation:
Answer:
Step-by-step explanation:
x³-6x²+11x-6
put x=1
1³-6×1²+11×1-6=1-6=11-6=0
by synthetic division
1| 1 -6 11 -6
| 1 -5 6
|----------------
| 1 -5 6 |0
x²-5x+6=0
x²-2x-3x+6=0
x(x-2)-3(x-2)=0
(x-2)(x-3)=0
x=1
x-1=0
so x³-6x²+11x-6=(x-1)(x-2)(x-3)
By using <span>De Moivre's theorem:
</span>
If we have the complex number ⇒ z = a ( cos θ + i sin θ)
∴
![\sqrt[n]{z} = \sqrt[n]{a} \ (cos \ \frac{\theta + 360K}{n} + i \ sin \ \frac{\theta +360k}{n} )](https://tex.z-dn.net/?f=%20%5Csqrt%5Bn%5D%7Bz%7D%20%3D%20%20%5Csqrt%5Bn%5D%7Ba%7D%20%5C%20%28cos%20%5C%20%20%5Cfrac%7B%5Ctheta%20%2B%20360K%7D%7Bn%7D%20%2B%20i%20%5C%20sin%20%5C%20%5Cfrac%7B%5Ctheta%20%2B360k%7D%7Bn%7D%20%29)
k= 0, 1 , 2, ..... , (n-1)
For The given complex number <span>⇒ z = 81(cos(3π/8) + i sin(3π/8))
</span>
Part (A) <span>
find the modulus for all of the fourth roots </span>
<span>∴ The modulus of the given complex number = l z l = 81
</span>
∴ The modulus of the fourth root =
Part (b) find the angle for each of the four roots
The angle of the given complex number =
![\frac{3 \pi}{8}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%20%5Cpi%7D%7B8%7D%20)
There is four roots and the angle between each root =
![\frac{2 \pi}{4} = \frac{\pi}{2}](https://tex.z-dn.net/?f=%20%5Cfrac%7B2%20%5Cpi%7D%7B4%7D%20%3D%20%20%5Cfrac%7B%5Cpi%7D%7B2%7D%20)
The angle of the first root =
![\frac{ \frac{3 \pi}{8} }{4} = \frac{3 \pi}{32}](https://tex.z-dn.net/?f=%20%5Cfrac%7B%20%5Cfrac%7B3%20%5Cpi%7D%7B8%7D%20%7D%7B4%7D%20%3D%20%20%5Cfrac%7B3%20%5Cpi%7D%7B32%7D)
The angle of the second root =
![\frac{3\pi}{32} + \frac{\pi}{2} = \frac{19\pi}{32}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%5Cpi%7D%7B32%7D%20%2B%20%20%5Cfrac%7B%5Cpi%7D%7B2%7D%20%3D%20%20%5Cfrac%7B19%5Cpi%7D%7B32%7D%20%20)
The angle of the third root =
![\frac{19\pi}{32} + \frac{\pi}{2} = \frac{35\pi}{32}](https://tex.z-dn.net/?f=%20%5Cfrac%7B19%5Cpi%7D%7B32%7D%20%2B%20%20%5Cfrac%7B%5Cpi%7D%7B2%7D%20%3D%20%20%5Cfrac%7B35%5Cpi%7D%7B32%7D%20%20)
The angle of the fourth root =
Part (C): find all of the fourth roots of this
The first root =
![z_{1} = 3 ( cos \ \frac{3\pi}{32} + i \ sin \ \frac{3\pi}{32})](https://tex.z-dn.net/?f=%20z_%7B1%7D%20%3D%203%20%28%20cos%20%5C%20%20%5Cfrac%7B3%5Cpi%7D%7B32%7D%20%2B%20i%20%5C%20sin%20%5C%20%5Cfrac%7B3%5Cpi%7D%7B32%7D%29)
The second root =
![z_{2} = 3 ( cos \ \frac{19\pi}{32} + i \ sin \ \frac{19\pi}{32})](https://tex.z-dn.net/?f=%20z_%7B2%7D%20%3D%203%20%28%20cos%20%5C%20%20%5Cfrac%7B19%5Cpi%7D%7B32%7D%20%2B%20i%20%5C%20sin%20%5C%20%5Cfrac%7B19%5Cpi%7D%7B32%7D%29)
The third root =
![z_{3} = 3 ( cos \ \frac{35\pi}{32} + i \ sin \ \frac{35\pi}{32})](https://tex.z-dn.net/?f=%20z_%7B3%7D%20%3D%203%20%28%20cos%20%5C%20%20%5Cfrac%7B35%5Cpi%7D%7B32%7D%20%2B%20i%20%5C%20sin%20%5C%20%5Cfrac%7B35%5Cpi%7D%7B32%7D%29)
The fourth root =
Yes because 6/18=1/3 and 2/6=1/3. Then 6/18=2/6